A RELAÇÃO ENTRE VILA VELHA-ES E A BAÍA DE VITÓRIA: LEITURAS E PROPOSTA DE REQUALIFICAÇÃO - Carli, Ludmila Jesus de; Assis, Leandro Camatta de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The waterfronts interventions can value and recover the contact of the city and its citizens with water, through the creation of new centralities, urban connections and quality publics. The city of Vila Velha - ES has little access physical and visual with a water front of the Baia de Vitoria, for historical, geographic and administrative reasons. Despite this limitings cenario, the margins of the bay exhibit natural riches and a significant historical and architectural heritage for the state that ratify the great urban capacity, cultural, economic and tourist capacity of the region. Thus, the present work consisted in the spatial reading of the water front of Vila Velha, on the margins of the Baia de Vitória and the presentation of a proposal of urban requalification, seeking a contribution to a better physical, urban and visual relation ship between Prainha de Vila Velha and the Baia de Vitória. Diagnoses were made through surveys, Field visits, mapping, analysis and physical, urban and visual identifications. The limited relationship between the city and the bay was confirmed, and a project was proposed that aimed to create public spaces and democratic urban facilities, modal connectivity and respect to the local context.